Factors Affecting The Financial Performance of State-Owned Enterprise Companies Listed on the IDX - Ilham, Mohammad; Prayogi, Ardan Wahyu; Prayogi , Raihan; Leon , Farah Margaretha (Universitas Muhammadiyah Sorong, 2024)
This study aims to identify variables that affect the performance of banking companies listed on the IDX. The addition of the Ownership Composition variable as an independent variable is a novel part of this research. This research method involves collecting data from 22 banking companies over a five year period (2018–2022), and applying data processing analysis using panel data regression analysis techniques. The research results found that the capital adequacy ratio had an effect on Bank Performance. Likewise with the variables Non-performing loans, Liquidity Ratio, Bank Size, Market power, Gross Domestic Product, Inflation rate, and Ownership Composition which influence the performance of banking companies. The implication for financial managers is to choose the best way to utilize assets to achieve business goals, especially to improve shareholder welfare. This research emphasizes how important company performance is for investors when choosing investment opportunities in banking companies.